The Phenomenon of Accelerated Acquisition of Hijaiyah Script Reading, and Challenges in Latin Alphabet Mastery among Children with Dyslexia (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2026)
Dyslexia is a specific learning disability that affects an individual's ability to read, write, and recognize written language symbols. This disorder is neurobiological, involving brain areas that regulate phonological and visual processing. An interesting phenomenon emerges when children with dyslexia show better ability in reading Arabic letters (Hijaiyah) compared to the Latin alphabet. This study aims to provide an in-depth description of the ease with which dyslexic children read Hijaiyah letters, despite difficulties with the Latin alphabet. Unlike previous studies that predominantly focus on deficits in Latin-based reading, this study offers a novel perspective by examining the contrasting proficiency of dyslexic children in reading Hijaiyah script and identifying the underlying spiritual and multisensory learning mechanisms. A qualitative approach with a phenomenological design was used to explore the subjective experiences of dyslexic children in the process of reading two different writing systems. Data were collected through semi-structured in-depth interviews, participatory observation, and documentation studies involving children, parents, classroom teachers, psychologists, and religious teachers (ustazah). Data analysis was conducted through reduction, categorization, and thematic interpretation to uncover the essential meanings of the experiences of the subjects. The results indicate that Hijaiyah letters are easier for dyslexic children to read because their learning process involves a multisensory religious approach, activating alternative learning pathways through auditory repetition, kinesthetic movement, and spiritual guidance. This condition fosters emotional calm, intrinsic motivation, and self-confidence in reading Hijaiyah letters compared to the Latin alphabet. Religious values and a spiritual learning environment play a crucial role in enhancing self-confidence and reducing academic anxiety in dyslexic children. This phenomenon suggests that spiritual and multisensory-based learning could be an effective intervention alternative for children with literacy difficulties.